From Text to Brain: A Convergence of Qur'anic Exegesis, Neuroscience, and Maqāṣid al-Sharī‘ah on the Prohibition of Khamr - Abdillah Safa; Ahmad Nabilul Maram; Jullul Wara (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2025)
This study revisits the prohibition of khamr through a multidisciplinary lens to address the challenges of modern addictive substance abuse. Its objective is to test the compatibility of the Qur'anic prohibition with evidence from neuroscience and toxicology, while simultaneously formulating a contextual Islamic legal framework. This study develops an epistemological convergence matrix that maps neurobiological and toxicological indicators as the ‘illah (effective cause) of law within the framework of Maqāṣid al-Sharī‘ah. The methodology combines a thematic exegesis (tafsīr mawḍū‘ī) of verses on khamr, a comparative analysis of five schools of jurisprudence (madhāhib), and a synthesis of laboratory data on the neurological, physiological, and social damage caused by alcohol, cocaine, heroin, and synthetic psychoactive substances. Validity is maintained through triangulation with experts in exegesis, neurology, and toxicology. The findings indicate an expansion of the definition of khamr from fermented beverages to the functional category of “any substance that envelops the intellect.” Brain imaging reveals a reduction in dopamine receptors and hypofunction of the prefrontal cortex; toxicological data show a narrow margin of exposure and systemic organ damage. A matrix based on Maqāṣid al-Sharī‘ah affirms that addictive substances simultaneously threaten the preservation of intellect (ḥifẓ al-‘aql), life (ḥifẓ al-nafs), property (ḥifẓ al-māl), progeny (ḥifẓ al-nasl), and religion (ḥifẓ al-dīn). The convergence of exegesis and science yields an integrated policy model: legal prohibition, neuroscience-based education, and spiritual rehabilitation proven to reduce relapse rates. This study concludes that the Qur'anic prohibition of khamr possesses strong empirical rationality, while also providing an ethical foundation for narcotics regulation in contemporary Muslim societies. The findings underscore the importance of sustained transdisciplinary dialogue to respond to the emergence of new synthetic substances and to evaluate the effectiveness of Maqāṣid-based policies.